In Potential Siliko Simulation of Clorogenic Acid in Coffea canephora to Transfering Macrophage Polarization of M1 in Tuberculosis Infection (Medico Legal Update, 2020)
The aim of this study to determine the potential of Coffea canephora by using chlorogenic acid (CGA)compound associated with macrophages polarization in tuberculosis condition. Exploration of compoundby using the Knapsack database and Dr. Duke. Analysis of CGA by using a PASS server with the resultsranged score 0-1 probability to be active score. Molecular binding docking receptor and ligand were usedAutodock PyrXv9.5 and interactions between molecules using CLUSPRO 2.2. Potential activities of CGAcompounds was 3,5-dicaffeoylquinic acid, feruloylquinic acid, and p-coumaroylquinic acid with Pa valueclose to 1, this indicates that the accuracy of prediction of antioxidant activity was quite high. The results ofdocking through the attachment pathway of several amino acids showed the potential for side methylationactivity ‘which is able to reduced DNMT1 activity thereby suppressing the anti-inflammatory process.Protein interactions based on affinity values were higher among DNMT1 and STAT1 bonds compared toSTAT6. The results of the study concluded that the active compound in Coffea canephora was involved inthe function of the immune system and it related to the inflammatory process. It is triggers the delivery ofantimicrobial cytokine signals and increased antioxidant, it is very necessary in healing tuberculosis diseaseprocess.